Pengembangan Media Pembelajaran Berbantuan Augmented Reality Pada Mata Pelajaran Informatika Kelas VII SMP - Farhan Rizalmi; Nofri Hendri; Darmansyah; Alkadri Masnur (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Learning to introduce Microsoft Word tools to seventh-grade junior high school students still faces obstacles due to the use of media dominated by teacher demonstrations and text modules, so students have difficulty distinguishing the functions of icons that have visual similarities. This study aims to develop Augmented Reality-assisted learning media on the introduction of Microsoft Word tools material and test the validity, practicality, and improvement in learning outcomes after its use. This study uses a research and development method (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through media and material validation sheets, practicality questionnaires, and pretest and posttest tests. Validation involved two media validators and one material validator, while the practicality and implementation tests were conducted on 32 seventh-grade students of SMP Negeri 21 Padang. The results showed that the media obtained media validation scores of 4.88 and 4.93 and material validation of 4.84 with a very valid category. Media practicality obtained an average score of 4.91 with a very practical category, while the analysis of learning outcome improvements based on the N-Gain value obtained a score of 0.74 with a high category. Thus, Augmented Reality-assisted learning media meets the valid and practical criteria and shows a high increase in learning outcomes after being used in Informatics learning on the introduction to Microsoft Word tools material.